UiTM and VISTAS inks MoU for education and research collaboration / Zakiah Mohd Noordin and Dr. Siti Syairah Mohd Mutalip - Mohd Noordin, Zakiah; Mohd Mutalip, Siti Syairah (Faculty of Pharmacy, 2023)
On 3rd February 2023, Universiti Teknologi MARA (UiTM) and Vels Institute of Science Technology and Advanced Studies (VISTAS) have signed a memorandum of understanding (MoU) in various fields focusing on collaboration to enhance education and research institutions' quality as well as sharing of information and expertise. The MoU was signed by UiTM Vice-Chancellor, YBhg. Prof. Datuk Ts. Dr. Hajah Roziah Mohd Janor and VISTAS's Registrar, Dr P. Saravanan. The signing ceremony was attended by representatives from both institutions including, Dr S. Sriman Narayanan, Vice Chancellor of VISTAS, Dr P. Shanmugasundaram, Director of the School of Pharmaceutical Sciences, VISTAS and Prof. Dato' Dr. Abu Bakar Abdul Majeed, Dean Faculty of Pharmacy, UiTM.